The Empiricist Impulse: Doers and Thinkers in Sixteenth-Century Spain - Portuondo María M. (HoST)
This essay explores the tension that existed between empiricism and the metaphysical underpinnings of Aristotelian natural philosophy in Spain during the sixteenth century. This tension was most apparent in the range of science practitioners described in this essay as “Doers” and “Thinkers.” Using the figures of cosmographer Andrés García de Céspedes, architect Juan de Herrera, and theologians Benito Arias Montano and Francisco Suárez, this essay explains how they engaged with the limitations, but also the strengths of pre-Galilean natural philosophy.